Redemption [large type] : Hunters - Reasoner, James (Wheeler Publishing, A part of Gale, Cengage Learning, 2013)
When a violent scuffle between buffalo hunters and a party of Indians puts Redemption in the middle of a range war, Marshal Bill Harvey must find a way to keep the town and its residents safe.